Emerging Norovirus GII.12 infection in 2010 in Northern Taiwan - Chi-Neu Tsai; Yu-Chung Chang; Hsun-Ching Chao; Yi-Hsiang Hsu; Yuan-Hung Wang; Shih-Yen Chen (Journal of the Formosan Medical Association)
Norovirus (NoV) has been an emerging pathogen of enteric infections in the post-rotavirus vaccine era. GII.4 have played a major role in NoV infections while other genotypes were reported in sporadic outbreaks. In this study, we reported novel variant NoV GII.12 outbreaks in 2010, Taiwan with their genomic analysis and clinical manifestations compared to GII.4 infections.There were 30.5% (29 out of 95 cases) with NoV infection. The most common genotype was GII.4 (22, 75.9%) followed by GII.12 (5, 17.2%) and GII.3 (2, 6.9%). Phylogenetic analysis showed that our GII.12 sequences were closely aligned with reference genomes identified in the United Kingdom and the United States of America. When compared to patients infected by GII.4 NoV, those with GII.12 infection experienced a lower frequency and shorter duration of diarrhea. Continued research is essential to unravel the intricate relationship between NoV genotypes and clinical outcomes, guiding public health interventions and therapeutic strategies.